Inhibition of invasion and MMPs by a nutrient mixture in human cancer cell lines: a correlation study - Roomi, M.W.; Monterrey, J.C.; Kalinovsky, T.; Rath, M.; Niedzwiecki, A. (Experimental Oncology, 2010)
The aim of this paper is to examine the correlation between in vitro MMP-2 and MMP-9 secretion and Matrigel invasion in 42 different human cancer cell lines (selected on the basis of organ malignancies) treated with a nutrient mixture (NM).